HUBUNGAN FEMALE ATHLETE TRIAD DENGAN PERUBAHAN SIKLUS MENSTRUASI DI PPLP PROVINSI MALUKU - Marsiline Pieter (JARGARIA SPRINT: Journal Science of Sport and Health, 2020)
Menstruation is derived from uterine bleeding as a sign that the tool implies fulfill its function, which happens every month regularly on a grown woman whois healthy and not pregnant. Female athlete triad is a combination of three interrelated conditions that are deviant behavior of food, menstrual disorder and osteoporosis. Purpose; to determine the relationship of the female athlete triad with menstrual cycle changes in PPLP Maluku Province. This research using cross sectional approach. The sampling technique is total sampling. Samples in this study were female athlete PPLP Maluku Province totaling 38 people. Data collection technique such as statistical test questioner using Chi-square with signification level (<0.05). The results showed that the relationship amenorrhea with menstrual cycle changes with the value of P = 0,001. Relations irregularities eating behavior with changes in the menstrual cycle with P= 0,010. Osteoporosis relations with changes in the menstrual cycle with P= 0,477 where (p <0.05). Conclusion; relationship amenorrhea, behavioral deviations eating menstrual cycle changes in PPLP Maluku Province. It is expected that youth advice agencies and olahraga, can give attention to the development and health of the athletes and the coaches to organize and prepare training schedule female athletes and improve insight not only improve performance in the championship but in knowledge about reproductive health.